Ahmed Glaucoma Valve with Adjunctive Amniotic Membrane for Refractory Glaucoma - Amini, Heydar (Ophthalmic Research Center, 2010)
PURPOSE: To evaluate the efficacy and safety of Ahmed Glaucoma Valve (AGV) implantation with adjunctive use of preserved amniotic membrane for surgical management of refractory glaucoma. METHODS: Seven patients (5 female subjects) with refractory glaucoma were included in the study. An AGV (model FP7) was implanted in the usual manner and was covered with two layers of cryopreserved human amniotic membrane. Intraocular pressure (IOP) and number of glaucoma medications before and after surgery, and complications were evaluated. RESULTS: Mean duration of follow-up was 16.8±4.6 months. Mean preoperative IOP was 31.7±4.4 mmHg which was reduced to 17.7±6.1 mmHg at final follow-up (P=0.01, Wilcoxon U test). Although the number of topical medications was also reduced (mean decrease of 0.85 drops), this decrease was not significant (P=0.10, Wilcoxon U test). None of the eyes developed encapsulation after surgery; only one case was complicated by posterior migration of the implant resulting in failure. CONCLUSION: Glaucoma shunt surgery using the AGV with adjunctive amniotic membrane seems to be a safe and effective procedure which may reduce the risk of bleb encapsulation in refractory glaucomas.